Successful Treatment of Posttransplant EBV-Associated Lymphoma and Plasmacytoma Solely Localized to the CNS - Per Boye Hansen; Signe Ledou Nielsen (Case Reports in Hematology)
Two patients with diabetic nephropathy were diagnosed with primary central nervous system posttransplant Epstein-Barr-virus-associated lymphoproliferative disorder (PTLD) 3 years after renal transplantation. The histological diagnoses of the isolated brain tumors were diffuse large B-cell lymphoma and plasmacytoma. Considerable co-morbidity precluded intensive chemotherapy. The first patient with lymphoid CD20+ PTLD had a partial resection of her tumor performed. She was treated with 4 weekly doses of rituximab, ganciclovir and prednisolone; the posttransplant immune suppression (tacrolimus) was reduced. After 4 weeks of treatment a magnetic resonance imaging (MRI) demonstrated complete regression of the CNS lesion. The patient continues to receive rituximab (every second month), valgangciclovir and low-dose prednisolone. Twenty-two months after initiation of therapy, she is still in complete remission. The second patient was only treated with craniospinal irradiation involving the medulla to the second cervical vertebra and valgangciclovir. Moreover, the posttransplant immune suppression was reduced. A new MRI two months after initiation of therapy showed a complete regression of the lesions in the CNS; this was again demonstrated by a MRI after 19 months. These 2 cases illustrate interesting alternative treatments of PTLD. To our knowledge, an EBV-associated PTLD of plasmacytic origin isolated to the CNS has never been described before.